Increasing Community Participation in Sustainable Urban Housing Renewal Implementation (Case Study: Sombo Walk-Up Flat) - Dian Purnamasari; I Ketut Aria Pria Utama; I Ketut Suastika (IPTEK Journal of Proceedings Series, 2018)
Urban housing renewal is one of the ways to solve housing problems such as environmental, social and economic degradation in the community. But housing problems is still found on post-renewal in social, economic, cultural and environmental aspects. This is probably happened because the local community is not holistically involved in the implementation of the development. This research uses qualitative method with purposive sampling technique. Data collection techniques through interviews to the original residents of Sombo walk-up flats, stakeholder and managers of Sombo walk-up flats and also conducted by field observations. Then, the analysis is using data triangulation. The results of this study indicate that community participation is still not done holistically in which the community is less empowered after urban housing renewal is done. Therefore local communities should be empowered to realize sustainable urban housing renewal